Excavating the ’waterpits in the mountain’: the archaeology of Shashe-Limpopo Confluence Area rain-hill rock tanks - Schoeman, M. H. (Southern African Humanities, 2009)
Rock tanks on the hills of the Shashe-Limpopo Confluence Area (SLCA) were incorporated into rain-control rituals. Not only was their occurrence an important component in the selection of rain hills, they also acted as receptacles for rain-control material culture and fauna. Cupules that mark all rain hills increase in density around rock tanks. The cupule density increase indicates that encounters with rock tanks were not brief visits in order to discard rain-refuse; rather they comprised longer encounters, during which repeated hammering engaged with and reconfigured both the rock tank and rain hill. The ’being’ and meanings of rock tanks were the product of hunter-gatherer and farmer knowledge about rain merging to form rain knowledge of the SLCA. Understanding of SLCA rain subsequently became entangled in the topographic features used in rain control, and the features and know-how merged into locational rain wisdom. Simultaneously, rain control played an important role in K2-Mapungubwe ideology and state formation. In this place and context, rock tanks became symbols of rain, but also symbols of the multifaceted SLCA society of the early second millennium.